The Role of Lurah Bumi Ayu in Improving Public Health - Nurmala Sari; Lili Suryani; Fazira Fazira; Nurmanzila Nurmanzila (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Public health is a fundamental pillar of regional development as it directly affects the quality of life, productivity, and social welfare of the community. At the local level, the village head (lurah) plays a strategic role in encouraging community participation and coordinating public health programs. This Community Service Program (PKM) aims to analyze the role of the village head in improving public health through a public administration approach in Bumi Ayu Subdistrict, Dumai City. The methods applied in this program include counseling, training, simulation, and free health screening services using an educational approach. The activity was conducted on July 20, 2024, at STIA Lancang Kuning Campus and involved more than 100 participants from various community groups. The results indicate an increased public awareness of the importance of regular health check-ups and early detection of non-communicable diseases such as hypertension, diabetes, cholesterol, and uric acid disorders. In addition, the program strengthened the roles of the village heads, Posyandu cadres, and PKK members in supporting community health services. The discussion reveals that the success of public health programs at the subdistrict level is strongly influenced by participatory, collaborative, and responsive local leadership. This PKM activity is expected to serve as a model for strengthening the role of local government in promoting sustainable community health development.